Output torque matching in a multi-speed electric vehicle - TROMBLEY; DOUGLAS E; POLLOCK; FREDERICK J (1997)
In an electrically driven vehicle having an automatic transmission for coupling motor output torque to at least one drivewheel through a selected one of at least a pair of speed ratios, a method of matching the post-shift output torque to the preshift output torque is disclosed whereby undesirable post-shift driveline disturbances such as driveline sag are eliminated and post-shift vehicle performance is not compromised due to changes in output torque.